EFL Students’ Perceptions Toward Instagram TV for Online Learning Media to Increase English Vocabulary During Covid-19 Pandemic - Gumelar, Hikmah Anggun; Asmara, Candra Hadi (Universitas Muhammadiyah Gresik, 2022)
This study aimed at students’ perceptions of Instagram as an educational platform to increase vocabulary learning using Instagram and focused on features Instagram TV as a media for online learning and teaching using experimental design. Pre-test and post-test multiple-choice questions were given to 50 participants from SMPN 15 Gresik with the same duration, media, and topic to measure EFL learners’ vocabulary development using experimental design and analyzed using quantitative and qualitative tests. There are 20 items of instruments used that were tested for vocabulary development as pre-test and post-test for quantitative data. Students also filled in the questionnaire using the English language with a total of 12 items related to the use of Instagram TV. For qualitative, interviews are obtained regarding student’s perceptions. The results showed that the students showed positive results and good feedback. In conclusion, the study recommends the use of Instagram TV as a media online learning that is effective to increase students' learning motivation for EFL learners to do online learning during the covid-19 pandemic.